PERTANGGUNGJAWABAN PIDANA ADVOKAT YANG MELAKUKAN PERBUATAN MENGHALANG-HALANGI PROSES PERADILAN TINDAK PIDANA KORUPSI - Saputra, Rozi Agus; Deliana, Evi; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Corruption eradication in Indonesia still faces many obstacles, some of which are caused by resistance from various parties. The number of actions that are blocking the judicial process of corruption. One of them is the action of an advocate who deliberately blocks the judicial process against his client. However, in the Corruption Act does not clearly regulate the criteria of conduct which is categorized as an act of obstruction of justice. In addition, an advocate feels that he cannot be held liable for criminal liability because of the inherent immunity rights in his profession.Research method / approach used by writer in this research is normative law research. The primary legal material used is Law Number 18 of 2003 concerning Advocates, Act Number 46 of 2009 concerning Corruption Criminal Court. Secondary Legal Material, in the form of a bill, research results, scientific work from the legal community and others, newspapers, internet, articles. Tertiary Legal Materials such as dictionaries, encyclopedias. Analysis of the data used is the analysis of qualitative data and describes it descriptively.From the research results it can be concluded that the obstruction of justice of the judicial process of corruption is not limited to just a few acts, the Actor only understands and knows that his actions can result in obstruction of the legal process, although in reality the legal process is not frustrated by his actions. And for advocates who commit acts to obstruct the criminal justice process of corruption, they must still be held accountable even though the company is protected by the rights of immunity because the rights of immunity still have limitations or are not absolutely valid.Keywords: Obstruction of justice, advocate, criminal liability.